Indicators of Husband's Role in Pregnancy and Maternity Care - Apik Indarty Moedjiono; Kuntoro Kuntoro; Hari Basuki Notobroto (International Journal of Public Health Science (IJPHS), 2017)
The maternal mortality rate (MMR) in developing countries is still a major health problem, including in Indonesia. Antenatal Care (ANC), delivery with skilled birth attendance (SBA) at the time of delivery and delivery in institutional are universally considered important for reducing maternal mortality. Husbands can play a crucial role in pregnancy and childbirth. Therefore, the aim of this study was analyze the indicators of husband's role in pregnancy and maternity care which were suspected as one of the determinants of   ANC and SBA use in Polewali Mandar Regency. The population of this prospective cohort study was all married and pregnant woman, before using contraceptives and contraceptive failure or not using contraception and pregnancy is planned, unplanned pregnancy or mistimed pregnancy in Polewali Mandar 2015 (Size of sample = 100). Samples were randomly selected from participants of screening in 12 sub-districts in Polewali Mandar. Data about husband's role in pregnancy and maternity care was obtained through interviews using a structured questionnaire data processing by using SMART-PLS.  The result of data analysis suggested that the coefficient value that has been standardized from each indicator were as follows: accessibility = 0.944 and engagement = 0.954, dan responsibility = 0.968. Indicators of organizational support in implementing Maternal and Child Health Information System at Polewali Mandar Regency, respectively from the most important are: responsibility, engagement, and accessibility.